ANALISIS EFEKTIVITAS PENGELOLAAN PIUTANG PADA PT XYZ - Siti Aisah; Titik Purwaningtyas; Istna Fibriyadi; Muntasir Muntasir (JURNAL LENTERA AKUNTANSI, 2026)
Optimal management and turnover of accounts receivable are essential for PT XYZ, a distribution company that implements a credit sales system, to maintain smooth cash flow. Against this background, this study aims to analyze the effectiveness of accounts receivable management and the analysis of accounts receivable turnover at PT XYZ from 2022 to 2024. The research method utilizes a descriptive quantitative approach with secondary data sources, where data collection methods were conducted through observation, interviews, and documentation. The analysis methods used in this study are the accounts receivable turnover ratio analysis and the average collection period ratio analysis. The results of the study show that the accounts receivable turnover rate of PT XYZ  decreased from 4.59 times in 2022, to 4.09 times in 2023, and further declined to 3.86 times per year in 2024, while the average collection period increased from 80 days to 89 days, and rose again to 95 days. It can be concluded that PT XYZ  has managed its accounts receivable turnover rate effectively, but the average age of receivables has increased annually